The clinical course of bronchiolitis associated with acute otitis media. Issue 4 (1st October 2000) - Shazberg, Gila; Revel-Vilk, Shoshana; Shoseyov, David; Ben-Ami, Anat; Klar, Aharon; Hurvitz, Haggit
Abstract : BACKGROUND: Acute otitis media (AOM) is the most common bacterial co-infection of viral bronchiolitis. AIMS: To evaluate the influence of AOM on the clinical course of bronchiolitis. SUBJECTS: 150 children younger than 24 months old, diagnosed with bronchiolitis, hospitalised between December 1997 and May 1999. METHODS: Body temperature, respiratory rate, oxygen saturation, and the need for oxygen supplementation were recorded on admission and daily throughout hospitalisation. Complete blood count, erythrocyte sedimentation rate, and assay for respiratory syncytial virus were performed on admission. All children were examined daily for the appearance of AOM. The clinical course of children with bronchiolitis and AOM was compared to those without AOM. RESULTS: AOM was diagnosed in 79/150 (53%) children with bronchiolitis. Most were diagnosed within the first two days of hospitalisation. No significant difference was found in the clinical and laboratory findings on admission and on daily follow up between children with and without AOM. CONCLUSIONS: This 2.5 year prospective study showed no difference in the course of bronchiolitis, whether an ear infection was present or not.